2020
DOI: 10.1007/s12288-020-01385-7
|View full text |Cite
|
Sign up to set email alerts
|

Tele-Medicine Services in Hematological Practice During Covid Pandemic: Its Feasibility and Difficulties

Abstract: In COVID 19 pandemic, delivery and access of health care services have become challenging. Telemedicine services can be considered for management of patients with hematological diseases. This study included all patients who enrolled for telemedicine facility for hematology from May 15 to July 15, 2020. Patient's demographic and disease related parameters were recorded during the teleconsultation call. Overall satisfaction of attending doctor and patients were also recorded. A total of 1187 teleconsultation app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Although the initial coagulopathy of COVID-19 usually presents with a prominent elevation of D-dimer and fibrin/fibrinogen-degradation products [ 6 ], these were not present in our patient. Rather, we found bleeding from gastric IFP to be the cause of the patient’s progressive anemia.…”
Section: Discussionmentioning
confidence: 72%
“…Although the initial coagulopathy of COVID-19 usually presents with a prominent elevation of D-dimer and fibrin/fibrinogen-degradation products [ 6 ], these were not present in our patient. Rather, we found bleeding from gastric IFP to be the cause of the patient’s progressive anemia.…”
Section: Discussionmentioning
confidence: 72%
“…Among these finalised articles, ten were published in 2020 [ 32 – 41 ], and nine were published in 2021 [ 42 – 50 ]. Included studies consisted of eleven cross-sectional studies [ 32 , 33 , 35 – 37 , 39 , 40 , 45 , 46 , 49 , 50 ] and eight cohort studies [ 34 , 38 , 41 44 , 47 , 48 ]. Studies covered the application of telehealth services for different medical issues, including ophthalmology ( n = 4) [ 32 , 39 , 41 , 46 ], neurology ( n = 4) [ 38 , 42 , 45 , 50 ], dermatology ( n = 2) [ 35 , 43 ], non-communicable diseases ( n = 4) [ 33 , 44 , 48 , 49 ], haematological illness ( n = 1) [ 37 ], orthopaedic issues ( n = 2) [ 36 , 47 ], respiratory illness ( n = 1) [ 34 ], and substance use disorders (SUDs) ( n = 1) [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8] e benefits of telemedicine have quickly become more evident in the context of the current crisis, especially given the heightened risk of COVID-19 infection and severity of symptoms among the patients suffering from hematological diseases including leukemia, lymphoma, bone marrow failures, immune thrombocytopenia (ITP), patients on immunosuppressives, thalassemia, and many more. [9,10] Shah et al [11] described that by changing practice and embracing telemedicine, they could protect their patient and personnel, minimize resource utilization, better utilization of staff for indoor COVID patients, and continue providing safe essential care. Researchers from the Houston Methodist Cancer Center have shown that during the current pandemic, overall 92.6% of patients and 65.2% of physicians were satisfied with video-based hematology/oncology services during the pandemic.…”
Section: Teleconsultation During Covid-19 Pandemicmentioning
confidence: 99%
“…A hematologist getting a call from the international space station to treat an astronaut's thrombus during a NASA mission is the example of ultimate telemedicine. [22] Kumar et al [10] from AIIMS (New Delhi, India) conducted a telemedicine feasibility study for various hematological patients and understood multiple factors responsible for a successful teleconsultation. During the COVID-19 pandemic, their tertiary care hospital started teleconsultation services for patients who could not attend the physical outpatient department.…”
Section: Teleconsultation During Covid-19 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation